The Influence of Discovery Learning on the Mathematical Problem-Solving Ability of Elementary School Students - Yeni Dwi Kurino; Tatang Herman; Turmudi Turmudi; Mohamed Nor Azhari Azman Azhari (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis research aims to determine the influence of discovery learning on the mathematical problem-solving ability of elementary school students. The research used a quasi-experimental method with two classes, namely the experimental class and the control class. The population used in this research was 64 fifth-grade elementary school students. The sampling technique was random, while data collection was carried out using pretest and posttest instruments. The research results show that the influence of discovery learning in mathematics learning has a significant impact on improving students' problem-solving abilities. The discovery learning model with competitive and collaborative group learning concepts creates an interesting and motivating learning environment for students. By implementing discovery learning, students become more involved and enthusiastic in learning mathematics. They participate actively in group games that involve discussion, teamwork, and joint problem-solving.Keywords: discovery learning, problem solving abilities, elementary school students. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh discovery learning terhadap kemampuan pemecahan masalah matematika siswa sekolah dasar. Penelitian ini menggunakan metode quasi eksperimen dengan dua kelas, yaitu kelas eksperimen dan kelas kontrol. Populasi yang digunakan pada penelitian ini adalah siswa kelas V sekolah dasar yang berjumlah 60 orang. Teknik pengambilan sampel secara acak, sedangkan pengumpulan data dilakukan dengan menggunakan instrumen pretest dan posttest. Hasil penelitian menunjukkan bahwa pengaruh discovery learning dalam pembelajaran matematika memberikan dampak yang signifikan terhadap peningkatan kemampuan pemecahan masalah siswa. Model discovery learning dengan konsep pembelajaran kelompok kompetitif dan kolaboratif menciptakan lingkungan belajar yang menarik dan memotivasi siswa. Dengan menerapkan discovery learning, siswa menjadi lebih terlibat dan antusias dalam pembelajaran matematika. Mereka berpartisipasi aktif dalam permainan kelompok yang melibatkan diskusi, kerja sama tim, dan pemecahan masalah bersama.Kata kunci: pembelajaran discovery, kemampuan pemecahan masalah, siswa sekolah dasar.